Cardio-Respiratory Function Among Formal Sector Workers At Agbogbloshie E-Waste Recycling Site In Accra, Ghana - Owusu-Sekyere, S.O. (University of Ghana, 2018)
Background: Crude dismantling and burning of e-waste as done at the Agbogbloshie recy-cling/dumpsite results in release of a myriad of toxic chemical substances such as heavy met-als dust, dioxins, furans, plume of smoke containing chemical intermediates such as polyhy-drogenated aromatic hydrocarbons and polycyclic aromatic hydrocarbons. Exposure to these toxic chemicals could impact negatively on both human and environmental health. Previous studies on exposure have mostly focused on either e-waste workers or contamination of the environment; air, water and soil, but not on formal workers around the e-waste site. Objective: The aim of this study was to assess cardio-respiratory function among formal workers at Agbogbloshie. Methods: This was a cross-sectional study involving apparently healthy office workers. A modified respiratory questionnaire was used to assess prevalence of respiratory symptoms among study participants. Also, spirometer, pulse oximeter, sphygmomanometer was used to take measurements of lung function, pulse rate and blood pressure. The data gathered was coded and entered into Excel Microsoft 2016 and exported to Stata version 15.0 for analysis. Means, medians, standard deviations and interquartile range was calculated for continuous variables as appropriate and spearman rank correlation was used to analyze the relationship between hours of work and lung function indices. Results: A total of 120 respondents were recruited for the study, 91(75.8%) were males and 29(24.2%) were females. The most common respiratory symptoms were common cold, cough and sneezing. Majority of the respondents had abnormal cardio vascular health indicators. There was a negative correlation between number of years worked (duration of work) or number of days worked and lung function as indicated by respiratory function indices (FEV1/FVC) by spirometry. Conclusion: This study showed a high prevalence of respiratory symptoms; a high preva-lence of blood pressure increments in the pre-hypertensive and hypertensive range and a sig-nificant association between the number of working hours and poor respiratory function indi-ces (FEV1/FVC) among formal sector workers at Agbogbloshie.
Thesis (MPhil)
Keywords: hazard; E-waste; occupational hazard; spirometer; lung function indices; pulse oximeter; sphygmomanometer; formal workers